Eu3+ doped lanthanum oxide nanowhiskers: microwave hydrothermal synthesis, characterization and photoluminescence properties - Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Kakade, Bhalchandra A.; Ravi, V.; Saaminathan, V. (Journal of Physics D-Applied Physics, 2006)
We report here a straightforward and rapid microwave - hydrothermal route providing an easy synthesis of Eu3+ doped La2O3 nanowhiskers. The nanostructured Eu3+ doped La2O3 is characterized by x-ray diffraction studies, scanning electron microscopy and photoluminescence (PL). The emission spectrum shows transitions from the excited 5D(0) state to F-7(J) (J = 0, 1, 2, 3, 4) levels of the Eu3+ ion. The most intense peak around 611 nm is due to the D-5(0) -> F-7(2) transition, expected from the Judd-Ofelt selection rules. PL spectra measurements demonstrate that the lanthanum oxide nanowhisker shows higher PL intensity.